Les magasins-entrepôts de Montréal, 1850 à 1880 : formes et fonctions commerciales. Un nouveau regard - Burgess, Joanne; Lauzon, Gilles (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Magasins

Art, artisanat et exotisme: magasiner des expositions - Boily, Hélène (Cap-aux-Diamants, 1995)
issued: 1995-24-00
Keywords: Expositions; Magasins

1927. Le magasin Eaton s'agrandit pour mieux vous servir! - Mathieu, Jocelyne (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Eaton; Magasins

Analyse des tendances de vol dans les grands magasins à Montréal - Mahy-Ma-Somga, Augustin (Université de Montréal, 1969)
Keywords: Criminalité; Magasins

Les logiques de localisation des magasins à grande surface: l'exemple de PriceCostco dans la région de Montréal - Palardy, Jonathan (Université de Montréal, 1999)
Keywords: Commerce de détail; Magasins

Conditions de travail dans les magasins à chaîne de l'épicerie; une étude comparative des conditions de travail dans deux chaînes de magasins de la cité de Montréal avec références aux heures de travail, à la structure des salaires et aux conditions physiques et psychologiques de travail. Comparaison: Dionne, Dominion, 1945-1950 - Lemire, Hubert (Université de Montréal, 1952)
Keywords: Magasins; Travail; Épicerie

Dupuis Frères: le magasin du peuple: plus d'un siècle de fierté québécoise - Dupuis-Leman, Josette (Stanké, 2001)
Keywords: Commerce de détail; Dupuis Frères; Magasins

Le magasin Dupuis Frères de Montréal: les transformations dans le temps et l'espace d'une institution urbaine, 1868-1978 - Turgeon, Alain (Université de Sherbrooke, 2005)
Keywords: Commerce de détail; Dupuis Frères; Magasins

Étalages, vitrines, services et nouveaux espaces. Trois grands magasins de Montréal durant les années 1920 - Comeau, Michelle (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Commerce de détail; Dupuis Frères; Eaton; Magasins; Morgan

3e étage! Manteaux et accessoires pour dames! L’ère des grands magasins au Québec - Lessard, Michel (Cap-aux-Diamants, 1995)
issued: 1995-24-00
Keywords: Commerce de détail; Dupuis Frères; Eaton; Magasins; Morgan; Simpson

DeSerres, une entreprise montréalaise - Bergeron, Normand (Il était une fois...Montréal-Nord, 2021)
issued: 2021-24-00
Keywords: Magasins

Omer DeSerres. Trois générations créatives - DeSerres, Hélène (Éditions de l'Homme, 2008)
Keywords: Magasins

La maison J. A. Gagnon - Hachey, Jean-Marie (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Magasins

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

"Behind the Store": Montreal Shopkeeping Families between the Wars - Taschereau, Sylvie (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Alimentation; Famille; Magasins

Origin and Evolution of the Department Store - Tamilia, Robert D. (Université du Québec à Montréal et Centre de recherche en gestion, 2002)
Keywords: Commerce de détail; Magasins

The Mail Order Catalogue : An Achievement in Mass Distribution and Labour - Willis, John (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Commerce de détail; Magasins

Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
issued: 2005-21-00
Keywords: Eaton; Femmes; Magasins

Le repositionnement du centre-ville de Montréal dans la structure commerciale régionale; un examen des comportements d'achat de ses travailleurs de bureau - Mercier, Charles-Olivier (Université de Montréal, 2006)
Keywords: Centre-ville; Magasins; Quartiers

La femme illustrée par Dupuis frères limitée - de Andrade, Marie-Maxime (Cap-aux-Diamants, 2018)
issued: 2018-21-00
Keywords: Dupuis Frères; Femmes; Magasins

Le centre commercial de l’île de Montréal: Typologie d’un espace commercial en construction, 1950-1955 - Dalcourt, Annie-Claude (Université du Québec à Montréal, 2012)
Keywords: Banlieue; Centres commerciaux; Magasins

Figures du libraire au Québec - Brisson, Frédéric (Documentation et bibliothèques, 2005)
issued: 2005-04/2005-06
Keywords: Beauchemin (librairie); Librairie; Magasins

Entrepreneuriat et travail dans un commerce engagé: exploration du sens et panorama des pratiques des acteurs - Jauzion, Catherine (Université du Québec à Montréal, 2008)
Keywords: Cafés; Magasins; Restaurant; Travail

Une grande aventure commerciale - Duhamel, Roger (s.é., 1963)
Keywords: Commerce de détail; Dupuis Frères; Magasins

Christmastime chez Dupuis Frères - Dupuis-Leman, Josette (The Beaver, 2005)
issued: 2005-12/2006-01
Keywords: Commerce de détail; Dupuis Frères; Magasins

Dupuis Frères, Montréal - Martel, Yves (Montréal en tête, 1998)
issued: 1998-22-00/1998-23-00
Keywords: Commerce de détail; Dupuis Frères; Magasins

Une amitié nécessaire: entraide et fraternité dans le champ des comic books québécois (1984-1995) - Rioux, Philippe (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 2020)
Keywords: Bande dessinée; Librairie; Magasins; Édition

Archambault au service des Québécois depuis 1896 - Bergeron, Normand (Il était une fois...Montréal-Nord, 2022)
issued: 2022-21-00
Keywords: Commerce de détail; Librairie; Magasins; Musique

Le mouvement montréalais pour la fermeture de bonne heure des commerces. Genre, classe et régulation sociale du temps à l'époque libérale (1885-1909) - Rudy, Jarrett (Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles), 2020)
Keywords: Commerce de détail; Magasins; Marchands; Travail

Working for Family, Nation and God: Paternalism and the Dupuis Frères Department Store, Montreal, 1926-1952 - Matthews, Mary Catherine (Université McGill, 1997)
Keywords: Commerce de détail; Dupuis Frères; Magasins; Travail

Famille, foi et patrie: le credo de Dupuis frères - Trudel, Robert (Cap-aux-Diamants, 1995)
issued: 1995-24-00
Keywords: Commerce de détail; Dupuis Frères; Magasins; Travail

Commerces du coin - Giroux, Éric (Écomusée du fier monde et arrondissement Ville-Marie, 2009)
Keywords: Commerce de détail; Magasins; Quartiers; Sainte-Marie

L'avenue du Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2024)
issued: 2024-21-00
Keywords: Magasins; Mont-Royal (rue); Plateau Mont-Royal; Tremblay; Michel

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Number: 2
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Corner of Victoria Avenue & Sherbrooke (The Westmount Historian, 2011)
Number: 2
Keywords: Banque Royale; Banques; Magasins; Rues; Sherbrooke (rue)

Victoria Avenue in Westmount (The Westmount Historian, 2010)
Number: 1
Keywords: Casernes; Gares; Logement; Magasins; Rues; Westmount; Épicerie

Branding ''the Bay/la Baie'': Corporate Identity, the Hudson's Bay Company, and the Burden of History in the 1960s - Opp, James (The Canadian Historical Review, 2015)
Number: 2
Keywords: Commerce de détail; Compagnie de la Baie d'Hudson; Magasins; Publicité

Un sentiment antijuif exploité par la publicité - Levesque, Sophie (Histoire Québec, 2015)
Number: 3
Keywords: Arcand; Adrien; Commerce de détail; Idéologies; Juifs; Magasins; Publicité

Alimentation, commerce et patrimoine: documenter les acteurs du Vieux-Montréal victorien 1850-1880 - Burgess, Joanne (Laboratoire d'histoire et de patrimoine de Montréal, 2016)
Keywords: Alimentation; Commerce de détail; Magasins; Patrimoine; Quartiers; Vieux-Montréal

Hormidas [Hormisdas] Laporte (1850-1934). Une petite maison, un grand homme - Cloutier, Gabrielle (Cahiers d'histoire du Sault-au-Récollet, 1993)
issued: 1993-23-00
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Héritage Dorval 2011 (Héritage Dorval, 2011)
Keywords: Bijouterie; Chaussure; Dentistes; Hôtellerie; Magasins; Quincaillerie; Restaurant; Électricité

Une petite maison... Un grand homme: Hormidas Laporte - Cloutier, Gabrielle (Montréal en tête, 2001)
issued: 2001-21-00
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Institutions commerciales de Verdun. D'hier à aujourd'hui (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Commerce de détail; Confection; Magasins; Quartiers; Quincaillerie; Verdun; Vêtements; Épicerie

Nourrir le quartier, nourrir la ville - Burgess, Joanne; Giroux, Éric (Écomusée du fier monde, 2017)
Keywords: Alimentation; Biscuiterie; Boulangerie; Brasserie; Centre-sud (quartier); Magasins; Marchés; Quartiers; Épicerie

Question sociale et citoyenneté: la dimension politique des régulations sociales (XIXe-XXIe siècles) - Petitclerc, Martin; Bienvenue, Louise; Niget, David; Verbauwhede, Cory (Presses de l'Université du Québec, 2020)
Keywords: Boscoville; Chômage; Commerce de détail; Crise; Délinquance; Enfants; Groupes populaires; Magasins; Marchands; Protestants; Travail

Commerces du Plateau: d'hier à aujourd'hui (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-24-00/2019-24-00
Keywords: Alimentation; Artisans; Bijouterie; Chaussure; Commerce de détail; Magasins; Mont-Royal (rue); Plateau Mont-Royal; Quartiers; Quincaillerie; Rues; Saint-Denis (rue); Saint-Laurent (rue); Épicerie